ISSUES IN HEALTHY AGEING AMONG AFRICAN RURAL WOMEN - C. N. , Prof. OkonkworOby (International Journal of Research -GRANTHAALAYAH, 2015)
Life expectancy has increased considerably and people are continually getting aware of the need to stay young, healthy, active and alive. In order to achieve these as one ages, we need to adopt a healthy life style and diet suitable for each stage of later life. The African culture has its uniqueness due to many factors including the extended family system (EFS) where one is totally dependent on the off-spring and relatives at old age. On the other hand women generally live longer than men thereby creating a situation that provides more old women and widows in the society. Furthermore, the same African culture (like the Igbos of Nigeria) do not encourage old widows to remarry or socialize, thereby placing more economic, socio-psychological and health challenges on the aged women especially in the rural setting where the younger ones have abandoned their villages to migrate to urban areas. The purpose of this paper is to discuss the issues of healthy aging among the African rural women. It is never too early or too late to work for healthy aging. Therefore, the health, social, psychological, economic and emotional aspect of life-style adjustment for aging .gracefully and happily shall be discussed. The paper ends with functional recommendations as strategies to equip individuals with useful skills for healthy, happy, active life as one ages.